Do companies with a competitive advantage make better use of IT? Evidence from Italian enterprises. (30th April 2008) - Neirotti, Paolo; Cantamessa, Marco; Paolucci, Emilio
This paper investigates whether or not companies with a competitive advantage make better use of Information Technology (IT) through a survey sent to Chief Information Officers (CIOs) in a cross-industry sample of 204 large Italian firms. Using structural equations modelling on data about the returns produced by IT between 2001 and 2004 in the companies analysed, this paper shows that in the manufacturing industries, firms with a competitive advantage ? thanks to their superior availability of organisational capabilities ? were more likely to use IT to improve their knowledge about customers and the performance of the new product development processes. Thus, by investing in IT, these companies were able to strengthen their preexisting advantage. Furthermore, by showing the importance of the effects on IT results due to structural variables such as industry, size of the firm and multinational origin, this paper underlines the importance of more carefully considering such effects (and especially those due to industry) in information systems research.